The Capability of Students to Collect Materials for Course Presentations Based on Project Learning - Danim, Sudarwan (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2023)
This study evaluated students' abilities in compiling lecture presentation materials based on project learning. The study was carried out at the Doctor of Education Program, FKIP Universitas Bengkulu. The subjects of this study were students of the doctoral program at FKIP Universitas Bengkulu who were taking the Leadership Development and Decission Making course. The results obtained, indicate that first, the ability of students to prepare lecture presentation materials for class meetings with a PjBL approach varies, and some of them do not even reflect the ideal PjBL. Second, there are still some gaps between their theoretical thinking and the reality on the ground to realize effective project-based learning. Third, the ideal PjBL model to be applied in fulfilling lecture achievements is only possible if there is sufficient time available, using a flexible academic calendar, and the participation of related parties.